The Influence Of Training, Competence And Work Environment On The Performance Of Civil Servants Of Satpol Pp And Damkar Of South Bengkulu Regency. - Pradesa, Ades; Soleh, Ahmad; Nurzam, Nurzam (Multidisciplinary Journals, 2024)
Human resources have good performance that can be influenced by the competence and training possessed by individuals, because performance cannot be separated from the quality of human resources themselves. In order to create professional and competent human resources, the company develops competency-based HR management. This type of research uses quantitative research. The analysis method in this study uses Validity test, Reliability Test, Multiple Linear Regression Analysis, Determination Coefficient and hypothesis testing using t test. The number of samples studied was 42 ASN Satpol PP and Damkar. The results of the multiple linear regression analysis are Equation Y = 10.788 + 1.277 X1 + 0.402 X2 + 0.229 X3 +e, this illustrates the positive direction of regression, meaning that the training variables (X1) and Competence (X2) and the work environment have a positive influence on employee performance (Y) at Satpol PP and damkar South Bengkulu Regency. The magnitude of the coefficient of determination from the calculation results using SPSS can be seen that the coefficient of determination of R square is 0.819. This means that the value of training (X1) and the value of competence (X2) affect employee performance (Y) by 81.9% while the remaining 19.1% is influenced by other variables not examined in the study.